Encouraging 'good' motherhood: self-tracking and the provision of support on apps for parents of premature infants. Issue 8 (11th June 2022) - Byrt, Adrienne; Dempsey, Deborah
ABSTRACT: In recent years, there has been an increase in the use of apps that support the transition to parenthood. Research on the experiences of parents of premature children who have returned home from hospital points to the need for ongoing support as they navigate the transition to parenthood without the support of neonatal intensive care staff. For parents of premature infants, these platforms can act as wellsprings of information and also provide emotional and instrumental support during extended periods of hospitalisation. We used the walk-through method to analyse the support content and self-tracking features of five market-leading apps aimed at new parents of premature infants. This content analysis revealed that none of the analysed apps featured ongoing support for parents once they have returned home with their infants. Further analysis of the sociocultural dimensions of the digital content revealed the implicit reinforcement of the gendered expectations of parenthood and heteronormative nuclear families, thereby suggesting that women must enact the majority of caregiving and implicitly excluding users from same-sex or single-parent families. This research illuminates the need for more inclusive and gender-neutral app design and content that can offer ongoing digital support to parents of premature infants who have returned home from hospital.